1996
DOI: 10.1016/s0380-1330(96)70961-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Freshwater Mussel Community of Lake St. Clair: from Unionidae to Dreissena polymorpha in Eight Years

Abstract: ABSTRACT. To determine density changes in both the zebra mussel, Dreissena polymorpha, and native mussels, Unionidae, in Lake St. Clair, surveys were conducted in 1990, 1992

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(65 citation statements)
references
References 39 publications
0
56
0
Order By: Relevance
“…The most recent year for which data are available is 2001 in a survey done by Hunter and Simons (2004). Data for the 1990s are from Nalepa et al (1996). Mean numbers of settled individuals/m2 + SE were: These numbers are typical of Dreissena spp.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent year for which data are available is 2001 in a survey done by Hunter and Simons (2004). Data for the 1990s are from Nalepa et al (1996). Mean numbers of settled individuals/m2 + SE were: These numbers are typical of Dreissena spp.…”
Section: Discussionmentioning
confidence: 99%
“…The direction of changes in population structure of mussels along a depth gradient in lakes can be related to changes in food limitation, habitat disturbance, and recruitment limitation with depth (Menge 1991, MacIsaac 1996a. For example, Nalepa et al (1996) found that mean shell length of Dreissena declined as water-column Chl a decreased between 1990 and 1994 in Lake St. Clair (see also Hunter and Simons 2004). The negative effect of Dreissena density on shell length (our study) and condition factor (RN, W. Goedkoop [Swedish University of Agricultural Sciences], U. Grandin (Swedish University of Agricultural Sciences), and PE, unpublished data) indicate that intraspecific competition might cause food limitation and, thus, the slower growth rates and smaller shell lengths of mussels in shallower area of lakes.…”
Section: ] Zebra Mussels Predation Physical Factors 449mentioning
confidence: 99%
“…Especially clear effects of its invasion were observed in lakes and rivers of N America, where the zebra mussel reached very high abundance. They included, among others, changes in trophic structure, in pathways of energy flow in the system, increased water transparency and changes in its chemistry, as well as decrease in chlorophyll concentration resulting from decreased phytoplankton density, changes in the structure of bacterio-, phyto-and zooplankton, increased abundance of bottom algae and changes in their communities, macrophyte development, and also some changes in fish and bottom macrofauna communities (among others GRIFFITHS 1993, HOL-LAND et al 1995, LOWE & PILLS-BURY 1995, NALEPA et al 1996, KURBATOVA 1998, STEVART et al 1998, JOHANSSON et al 2000, IDRISI et al 2001, MAYER et al 2001.…”
Section: Effect Of D Polymorpha On Other Molluscs and The Whole Macrmentioning
confidence: 99%
“…The zebra mussel can affect various components of aquatic ecosystems and their functioning to a considerable extent. The effect of the mussel on the structure and abundance of the benthic communities was studied by many authors (among others DERMOTT et al 1993, GRIFFITHS 1993, STEWART & HAYNES 1994, HOWELL et al 1996, NALEPA et al 1996, STEWART et al 1998, SHCHERBINA 2000, PEROVA & SHCHERBINA 2001; most of the papers pertained to lake ecosystems.…”
Section: Introductionmentioning
confidence: 99%